Gender inequality in the Nobel Prizes winners 1901-2020 - Delgadillo Álvarez, Dulce María del Carmen (2021)
Female participation in scientific research has been undervalued. This is demonstrated on the Nobel Prize, the highest award given to honor the work of eminent figures from the academic world. There is an evident gender inequality in the annual granting of this distinction because, from 1901 to 2020, only 23 women have obtained it in scientific areas and only three of them have won it alone since the rest have shared it. This is partially due to the few opportunities’ women had in the last century to access higher education and to conduct scientific research and, although this has changed over the years until the dawn of the new millennium, the number of female scientists is still low. The objective of this work is to perform a review of the achievements of some women scientists throughout history and to show the little recognition that they have been given. Specifically, in the case of the recognition of women scientists from the 20th century, the data registered on the Nobel Prize website (The Nobel Prize, 2021) were extracted and an analysis was carried out to determine the frequency with which the award has been given to women in the areas of physics, chemistry, and physiology or medicine. A brief bibliographic review was also accomplished on the work of the winners, as well as some eminent women who dedicated their lives to science and who had important achievements in it, although they were not recognized at their time.